Legal Support of the Patient’s Right to Innovation in Health - Shevchuk, Oleksandr; Lysodyed, Oleksandr; Borysenko, Igor; Bululukov, Oleg; Babaieva, Oleksandra (European Journal of Sustainable Development, 2020)
The article discusses certain aspects of legal regulation of patients’ rights to innovations in healthcare sector. The subject of the study is the legislative acts on human rights in healthcare field, forms and types of human rights and directions for their implementation. Attention is focused on such types of patients’ rights to innovations in healthcare field: (1) right to biomedical experiments; (2) right to reproductive technology; (3) right to donation; (4) right to transplant organs and anatomical materials; (5) right to therapeutic cloning; (6) right to change gender; (7) right to virtual reality. Essence of “innovation in medicine” is revealed, classification of human rights is given. The purpose of the article is to disclose the features of legal regulation of implementation of the patients rights to innovations in healthcare field. The methodology of this work is based on a set of research methods. The comparative method was used to elucidate the legal aspects of the patients rights to innovations in healthcare sector. Using the method of theoretical analysis, systemic and analytical methods, the term “patients’ rights to innovations in healthcare field” was established, their varieties were characterized. Introduction of effective innovative models in health sector in context of patient rights will improve the availability and quality of provision of medical services to the population. It has been established that an important element in the implementation of innovative technologies in healthcare sector is the regulatory framework, which must comply with international standards. Key words: health sector, innovation, legal regulation, patient rights